Prognose und Lebensqualität nach Entlastungstrepanation: eine deutschlandweite Erhebung zu den Einstellungen von Ärzten und Krankenpflegepersonal = Prognosis and quality of life after decompressive hemicraniectomy - Schwarz, Stefan; Kühner, Christine (Der Nervenarzt, 2011)
Decompressive hemicraniectomy reduces mortality in patients with space-occupying MCA infarction. Quality of life in surviving patients is discussed controversially. We assessed attitudes of neurologists and nurses providing care to this patient group towards decompressive hemicraniectomy.MethodsA postal questionnaire on attitudes and opinions on prognosis and quality of life after decompressive hemicraniectomy was returned by 280 neurologists and 166 nurses from tertiary care centers throughout Germany.ResultsIn both groups of professionals, estimates of the probability of survival after decompressive hemicraniectomy and the resulting degree of disability were consistent with results of clinical outcomes studies. Only 9% of the nurses and 33% of the physicians assumed that the majority of survivors achieve an acceptable quality of life; 58% of physicians and 32% of nurses would suggest decompressive hemicraniectomy to their nearest relative. Under the assumption of an uncertain outcome, 61% of physicians and 22% of nurses would agree to decompressive hemicraniectomy. In both professional groups, agreement for surgery increases when scenarios with a more favorable outcome were proposed [modified Rankin Scale (mRS) 2-5)]. If an outcome of 4 on the mRS is proposed, indicating moderately severe disability, only a minority favored decompressive hemicraniectomy (25% of doctors and 8% of nurses).ConclusionsDespite a realistic assessment of prognosis after decompressive hemicraniectomy, a majority of respondents estimated the quality of life of survivors as unsatisfactory. Nurses had a more pessimistic attitude towards decompressive hemicraniectomy. The majority of respondents consider an outcome of 4 on the mRS as unacceptable.